Analisis Perbedaan Pembacaan Kalibrator Temperatur dengan Drywell Menggunakan Uji Wilcoxon - Choirunnisa, Anis; Kuswantori, Ari; Rizki Nurhasan, Muhamad; Putra, Hagi Sugara (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2025)
The oven calibration process is a crucial step in ensuring the accuracy of temperature testing on tire components. At the PT XYZ DKM Plant, oven calibration is still performed externally due to the lack of a nine-point temperature calibrator compliant with AS 2853. This impacts calibration time and costs. Therefore, this study aims to design and analyze the performance of a nine-point temperature calibrator compared to the AIS-TCL-3 master temperature calibrator. The test was conducted at a temperature range of 30°C to 150°C with a minimum of 30 data points per point. The results were then analyzed using normality tests, Wilcoxon test, and Cohen's d test. The Wilcoxon test results showed no statistically significant differences between the designed instrument and the master instrument. Furthermore, all measurement values were within the ±1°C tolerance limit as per ASTM D1509-15 standard. This is supported by the Cohen's d value, which indicates a low to moderate difference in effect. Thus, the designed calibrator tool is declared suitable for use in internal calibration processes and can be an economical solution for the company.